2020
DOI: 10.5334/cie.6
|View full text |Cite
|
Sign up to set email alerts
|

The Art of Coaching: Addressing Mobile Technology Integration in a Complex Hospital School Environment

Abstract: This qualitative study examined the effects of a coaching program as part of a professional development effort to support integration of mobile technologies in a hospital school setting. The professional development consisted of two components: (a) the researchers introduced pedagogical models for incorporating mobile technology in education and (b) a technological expert (the iCoach) provided one-on-one and small-group personalized coaching. After studying the contextual challenges and teachers' needs over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Both Keehan and Hen remark that hospital teachers need to be incredibly proactive and flexible to provide for their diverse set of students by accessing an array of curricular knowledge, often in an impromptu fashion. This view is validated in a number of studies (Perry et al, 2014;Maor et al, 2020;Hen, 2020;Keehan, 2021). Their planned lessons often need to be differentiated on the fly in order to meet both the changing emotional and educational requirements of the child with medical needs (Capurso & Dennis, 2017;Benigno & Fante, 2020;Keehan, 2021).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Both Keehan and Hen remark that hospital teachers need to be incredibly proactive and flexible to provide for their diverse set of students by accessing an array of curricular knowledge, often in an impromptu fashion. This view is validated in a number of studies (Perry et al, 2014;Maor et al, 2020;Hen, 2020;Keehan, 2021). Their planned lessons often need to be differentiated on the fly in order to meet both the changing emotional and educational requirements of the child with medical needs (Capurso & Dennis, 2017;Benigno & Fante, 2020;Keehan, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…Benigno & Fante's 2020 study looking at the professional relationships of hospital teachers, found that compared to their mainstream colleagues, hospital school teachers must work within a far more complex web of relationships. Six of the studies point out that in addition to their students and colleagues, hospital teachers have daily interactions with parents, a variety of medical staff and teachers from the student's base school (Keehan, 2021;Hen, 2020;Benigno & Fante, 2020;McCarthy et al, 2017;Äärelä et al, 2018;Maor et al, 2020). Keehan reports that they must also work as part of a teaching team and collaborate with their colleagues daily unlike their traditional classroom counterparts.…”
Section: Interpersonal and Communication Skillsmentioning
confidence: 99%
See 3 more Smart Citations